The Realization of Formulaic Competence in the Classroom Interactions among Learners in Kampung Inggris Pare - Luluk Khoiriyah; Januarius Mujiyanto (English Education Journal, 2022)
A critical component in communicative competence is formulaic competence, enabling learners to create natural and fluent spoken and written texts. This competence refers to recurrent fixed expressions used by native speakers to communicate in daily life, such as collocations, idioms, lexical bundles, and insert/routines. This study aimed to investigate the formulaic expression by exposing Celce-Murcia (2007) and Biber et al.'s (1999) theory in the classroom interactions among learners in Kampung Inggris Pare. In addition, it used Lennon's (1990) theory to investigate the influence of formulaic language on the learners' fluency. A qualitative approach, exposing conversational analysis, was adopted to analyze the gathered data to fulfill the research objectives. The data were collected by observing the learners' interactions, including recording during the conversation. Thus, the current study reveals that Kampung Inggris, Pare learners produced all types of formulaic expressions. However, due to a lack of collocational awareness, they made simple combinations and tended to avoid more complex words with more than two particles. In addition, the learners who produced many formulaic expressions have high exclusive rates implying that the more formulaic expressions are used, the higher the fluency level will be obtained.